2010
DOI: 10.1088/1674-1056/19/8/080516
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation theory of spin-3/2 Ising system near phase transition temperatures

Abstract: Dynamics of a spin-3/2 Ising system Hamiltonian with bilinear and biquadratic nearest-neighbour exchange interactions is studied by a simple method in which the statistical equilibrium theory is combined with the Onsager's theory of irreversible thermodynamics. First, the equilibrium behaviour of the model in the molecular-field approximation is given briefly in order to obtain the phase transition temperatures, i.e. the first-and second-order and the tricritical points. Then, the Onsager theory is applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…It is worthwhile to stress that even though the divergence of τ gets pushed away from the critical temperature when the absolute value of the On-sager rate coefficient decreases, there exists a qualitative consistency between their thermal variations. Aforementioned behaviors are in accordance with the previously published studies [19][20][21][22][23][24]. On the other hand, Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is worthwhile to stress that even though the divergence of τ gets pushed away from the critical temperature when the absolute value of the On-sager rate coefficient decreases, there exists a qualitative consistency between their thermal variations. Aforementioned behaviors are in accordance with the previously published studies [19][20][21][22][23][24]. On the other hand, Fig.…”
Section: Resultssupporting
confidence: 92%
“…Recently, spin-1 Ising model has been analyzed by Erdem and Keskin within the framework of the entropy production [19,20] and it is found that one of the relaxation times diverges at the continuous phase transition point while the other relaxation time remains finite. The relaxation process of the pure spin-3/2 Blume-Emery-Griffiths (BEG) model with bilinear and biquadratic exchange interactions has been analyzed near the critical [21] and multicritical points [22]. In addition, thermal variations of the relaxation time of a metamagnetic Ising model has been investigated by Gulpinar et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…For the ferromagnetic interaction, a short range order parameter as well as the long range order is introduced (Tanaka et al, 1962;Barry, 1966) while there are two long range sublattice magnetic orders and a short range order in the Ising antiferromagnets (Barry & Harrington, 1971). Similarly the number of thermodynamic variables (order parameters) also increases when the higher order interactions are considered (Erdem & Keskin, 2001;Gülpınar et al, 2007;Canko & Keskin, 2010). For a general formulation of Ising spin kinetics with a multiple number of spin orderings ( i  ), the Gibbs free energy production is written …”
Section: Thermodynamic Description Of the Kinetic Modelmentioning
confidence: 99%
“…Grandi et al discussed dynamic critical exponents using the Monte Carlo simulations and short-time dynamic scaling [18]. Keskin and Canko studied the dynamic behavior of spin-3/2 Ising model through the path probability method [19,20] and the Onsager theory of irreversible thermodynamics [21,22]. Keskin et al investigated the dynamic phase diagram of spin-3/2 Ising model under an oscillating magnetic field by the use of the mean-field theory (MFT) [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%